Identification of 11-amino acid peptides that disrupt Notch-mediated processes in Drosophila. - Pi, H.; Huang, Y.C.; Chen, I.C.; Lin, C.D.; Yeh, H.F.; Pai, L.M. (Journal of Biomedical Science, 2011)
The conserved Notch signaling pathway regulates cell fate decisions and maintains stem cells in multicellular organisms. Up-regulation of Notch signaling is observed in several types of cancer and is causally involved in proliferation and survival of cancer cells. Thus, it is of great interest to look for anti-Notch reagents for therapeutic purposes. In model animal Drosophila, Notch signaling restricts selection of sensory organ precursors (SOPs) during external sensory (ES) organ development. To look for novel genes that can suppress Notch signaling, we performed a gain-of-function modifier screen to look for genes that enhance the phenotype of ectopic ES organs induced by overexpression of phyllopod, a gene required for SOP specification.From the gain-of-function screen, we discovered that overexpression of polished rice/tarsal-less (pri/tal) increases the numbers of ES organs as well as SOPs. pri/tal is a polycistronic gene that contains four short open reading frames encoding three 11-amino acid and one 32-amino acid peptides. Ectopic expression of the 11 amino-acid peptides recapitulates the pri/tal misexpression phenotype in ectopic ES organ formation. In situ hybridization experiment reveals that pri/tal mRNA is expressed in the SOPs of the chemosensory organs and the stretch-sensing chordotonal organs.In Drosophila wing development, the Notch signaling pathway mediates the formation of the dorsal-ventral (DV) compartmental boundary and the restriction of the vein width from the primordial veins, the proveins. We also found that pri/tal mRNA is expressed in the DV boundary and the longitudinal proveins, and overexpression of Pri/Tal peptides disrupts the DV boundary formation and helps to expand the width of the wing vein. Genetic analyses further show that a Notch loss-of-function allele strongly enhances these two phenotypes. Cut and E(spl)m? are target genes of the Notch pathway in DV boundary formation and vein specification, respectively. We also found that overexpression of Pri/Tal peptides abolishes Cut expression and co-expression of Pri/Tal peptides with phyl strongly reduces E(spl)m? expression.We show for the first time that the overexpression of Pri/Tal 11-amino acid peptides disrupts multiple Notch-mediated processes and reduces Notch target gene expression in Drosophila, suggesting that these peptides have novel antagonistic activity to the Notch pathway. Thus, our discovery might provide insights into designing new therapeutic reagents for Notch-related diseases.